Cloud native network creating a new era of intelligent application - Xiaolan WAN; Jinglin LI; Kebin LIU (Dianxin kexue)
With the continuous emergence of new applications such as holographic multimedia, integration of space, air and ground, metaverse and social Internet of things, the development of business applications moved towards digitalization, integration, bandwidth and intelligence, which correspondingly puts forward new demands for the transformation of the network.Through the research and analysis of future network characteristics, combined with the characteristics of the cloud native network, the cloud native advantage can be used to meet the needs of current hot business applications.The general architecture of the cloud native network was proposed.The capabilities of data plane, control plane and management plane were defined.Finally, the typical and hot application cases of the cloud native network were given.